Multiterminal Josephson Effect - Natalia Pankratova; Hanho Lee; Roman Kuzmin; Kaushini Wickramasinghe; William Mayer; Joseph Yuan; Maxim G. Vavilov; Javad Shabani; Vladimir E. Manucharyan (Physical Review X, 2020)
We report a probable observation of the dc Josephson effect in mesoscopic junctions of three and four superconductors. The devices are fabricated in a top-down fashion from a hybrid semiconductor-superconductor InAs/Al epitaxial heterostructure. In general, the critical current of an N-terminal junction is an (N-1)-dimensional hypersurface in the space of bias currents, which can be reduced to a set of critical current contours. The geometry of critical current contours exhibits nontrivial responses to electrical gating, magnetic field, and phase bias, and it can be reproduced by the scattering formulation of the Josephson effect generalized to the case of N>2. Besides establishing solid ground beneath a host of recent theory proposals, our experiment accomplishes an important step toward creating trijunctions of topological superconductors, essential for braiding operations.